EFFICIENCY OF OVATIDE ON MASS SEED PRODUCTION OF CLIMBING PERCH (Anabas testudineus, BLOCH, 1972) IN NALBARI DISTRICT, ASSAM - ANKUR RAJBONGSHI,; A. ALI,; M. CHAKRAVARTY,; M. DEKA,; H. MAZUMDAR,; PRANAB KR DAS,; S. BAISHYA, (The Bioscan, 2020)
A study was carried out to evaluate the efficiency of synthetic hormone (ovatide) on induce spawning of the climbing perch, Anabas testudineus under agro-climatic conditions of Assam. The breeding programme was conducted with 3 Ovatide doses of 0.1, 0.2 and 0.3 ml/kg body weight on performance of egg quality. After spawning, the fecundity of each cycle was calculated through relative fecundity and percentage of ovulation, fertilization, hatching and survival. All the three hatcheries (H-1, H-2, H-3) differed significantly (p<0.01) in performance of induced breeding while H-3 performed comparatively better (p<0.05) than the other two hatcheries. The brooder fishes injected with higher dose of Ovatide (0.3 ml/kg body weight) resulted in highest percentage of fertilization, hatching and survival rate as 98.03±0.74, 87.98±0.82, 80.92±0.94 in H-3 hatchery respectively while the lowest performance was observed in H-2 hatchery. The results showed that the synthetic hormone (Ovatide) is more effective for mass seed production of A. testudineus when injected with 0.3 ml/kg body weight.